Bridging Internship Design and Practice: A Multi-Stakeholder Cipp Evaluation of Teacher Competency - Prasetiyo Prasetiyo; Dini Rakhmawati; Yuli Kurniawati Werdiningsih (CV. Creative Tugu Pena, 2026)
Educational internship programs play a critical role in developing teacher competency by integrating theoretical knowledge and classroom practice. However, gaps between program design and field implementation, particularly in student readiness and stakeholder coordination, remain a challenge. The current mixed-method evaluative research examined the effectiveness of the internship program based on the CIPP model, covering context, input, process, and product from a multi-stakeholder perspective. The researchers took 1,314 respondents consisting of supervising lecturers, mentor teachers, and students. The researchers collected the data from a validated and reliable questionnaire. Then, the researchers examined the data with descriptive statistics and one-way ANOVA. The results found the high effectiveness of the internship program, 85.2%. The strongest performance was observable in the process (84.6%) and product (89.0%). In terms of the input dimension, starting from student readiness and classroom management skill, the obtained score is 79.6%. This percentage indicates the preparatory phase is a determinant dimension for further optimization. The ANOVA test yields a significant difference among stakeholders. This result highlights the effectiveness of stakeholder alignment toward the internship program. It implies the need to strengthen preparatory systems, supervision practices, and university–school collaboration to support sustainable teacher competency development.